2020
DOI: 10.1159/000510029
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Topical β-Blockers in Treating Infantile Hemangiomas: A Meta-Analysis Including 11 Randomized Controlled Trials

Abstract: <b><i>Background:</i></b> To evaluate the efficacy and safety of topical β-blockers in the treatment of superficial infantile hemangiomas (SIH) and mixed infantile hemangiomas (MIH), respectively, and compare the efficacy and safety of topical β-blockers with other interventions. <b><i>Methods:</i></b> The PRISMA guidelines were adhered to. We searched for randomized controlled trials in databases from 2010 to 2018 comparing topical β-blockers with other interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
2
19
0
1
Order By: Relevance
“…Ariwibowo, Danarti et al and associates found that Timolol maleate 0.5% the answer was better than corticosteroids in reducing the dimensions of superficial IH. 10,14,[17][18][19][20][21][22][23][24] Our study also showed reduction in size,colour and shape of superficial infantile hemangiomas in approximately 08-12 weeks after the initiation of treatment.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 68%
“…Ariwibowo, Danarti et al and associates found that Timolol maleate 0.5% the answer was better than corticosteroids in reducing the dimensions of superficial IH. 10,14,[17][18][19][20][21][22][23][24] Our study also showed reduction in size,colour and shape of superficial infantile hemangiomas in approximately 08-12 weeks after the initiation of treatment.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 68%
“…Several reports have described similar outcomes using topical beta-blockers for the treatment of superficial periocular IH and two large recent meta-analyses, involving 1235 and 2098 children, concluded that topical beta-blockers may replace oral propranolol as first-line treatment for superficial IH due to its comparable effectiveness and reduced adverse effects [8,9].…”
Section: Discussionmentioning
confidence: 92%
“…Oral propranolol and topical beta-blockers are an established treatment for proliferating infantile hemangiomas due to vasoconstrictive and angiogenesis-inhibiting effects. 3 , 4 Similarly, there are case reports of propranolol improving other vascular diseases such as arteriovenous malformations, 3 cavernous hemangioma, 5 angiolymphoid hyperplasia with eosinophilia, 6 pyogenic granuloma, 7 angiosarcoma, 8 KS, 9 and other reactive angiomatoses (reactive angioendotheliomatosis and graft-versus-host disease-associated angiomatosis). 4 Regression of classic KS lesions treated with topical β-blocker has been noted.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 Similarly, there are case reports of propranolol improving other vascular diseases such as arteriovenous malformations, 3 cavernous hemangioma, 5 angiolymphoid hyperplasia with eosinophilia, 6 pyogenic granuloma, 7 angiosarcoma, 8 KS, 9 and other reactive angiomatoses (reactive angioendotheliomatosis and graft-versus-host disease-associated angiomatosis). 4 Regression of classic KS lesions treated with topical β-blocker has been noted. 10 Propranolol can be employed to treat a wide range of abnormal vascular changes similar to PKS, such as proliferating infantile hemangioma and other vascular diseases.…”
Section: Discussionmentioning
confidence: 99%